Monitoring Komunikasi Program MBKM pada Mahasiswa Universitas Al Azhar Indonesia - Gunawan, Imsar; Sunuantari, Manik; Santi, Kussusanti; Soraya, Soraya; Hasna, Safira; Sepang, Nurul Robbi (Jurnal Al Azhar Indonesia Seri Ilmu Sosial, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) program aims to prepare students to achieve careers in the future according to their aspirations. With MBKM, students have the opportunity to be independent in building their competencies by learning directly from practical experience in the industry in synergy with the campus academic system. This study aims to measure the quality of communication in the MBKM program, using the concepts of comprehension, conviction, and satisfaction. The research method used is descriptive quantitative, with 65 respondents participating in the MBKM Universitas Al Azhar Indonesia in 2021. The results show that students understand well the information about MBKM delivered by the supervisor and the organizing committee. They believe that the information is appropriate, clear, and correct, and have satisfaction with the MBKM information they receive.Keyword: MBKM; Monitoring; Communication quality; Communication satisfaction